Identification of RT-PCR-Negative Asymptomatic COVID-19 Patients via Serological Testing - Wu, Jinru; Liu, Xinyi; Zhou, Dan; Qiu, Guangqian; Dai, Miao; Yang, Qingting; Pan, Zhonghui; Zhou, Ning; Wu, Pa (Frontiers in Public Health, 2020)
Asymptomatic individuals with coronavirus disease (COVID-19) have been identified via nucleic acid testing for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2); however, the epidemiologic characteristics and viral shedding pattern of asymptomatic patients remain largely unknown. In this study, serological testing was applied when identifying nine asymptomatic cases of COVID-19 who showed persistent negative RT-PCR test results for SARS-CoV-2 nucleic acid and no symptoms of COVID-19. Two asymptomatic cases were presumed to be index patients who had cleared the virus when their close contacts developed symptoms of COVID-19. Three of the asymptomatic cases were local individuals who spontaneously recovered before their presumed index patients developed symptoms of COVID-19. This report presents the epidemiologic and clinical characteristics of asymptomatic individuals with SARS-CoV-2 infection that were undetected on RT-PCR tests in previous epidemiologic investigations probably due to the transient viral shedding duration.